Advisory Board (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
Philipp Assinger, AustriaMaria Alejandra Martinez Barrientos, BoliviaDeb Carr, AustraliaLisa D’Adamo-Weinstein, United StatesRusty Dolleman, United StatesMeredith Hatch, United StatesDae Joong Kang, South KoreaBecky Klein-Collins, United StatesFjóla María Lárusdóttir, IcelandCharlotte Nitardy, United StatesRekha Rambharose, South AfricaCatherine Wanjiru, KenyaLaura Widger, Ireland